The Social Dilemma in Short Film: A Study of Pierre Bourdieu's Sociology - Utami, Lia; Zustiyantoro, Dhoni; Nugroho, Yusro Edy (Universitas Negeri Semarang, 2025)
This article examines the social dilemmas that emerge in the Javanese short film Weweh, produced by Sanggar Ori Gunung Kidul, using the perspective of literary sociology through Pierre Bourdieu's theory, especially the concepts of habitus, capital, arena, and symbolic violence. This study aims to identify the social dilemmas in the short film Weweh and the factors that cause them. The data analysis method in this study uses the semiotic method to interpret the signs and interpret them through hermeneutics. The results of the analysis show that there are two primary forms of social dilemmas, namely unrequited kindness and unfulfilled social expectations. Meanwhile, the factors that cause social dilemmas include economic inability, social disorganization, and moral dilemmas. These findings illustrate how social structures and individual positions in the social arena influence the experience of social dilemmas and how symbolic violence reinforces the tensions that occur. Thus, the film Weweh reflects the complexity of social relations and societal power dynamics.